2014
DOI: 10.1094/mpmi-01-14-0012-r
|View full text |Cite
|
Sign up to set email alerts
|

Redox Systems in Botrytis cinerea: Impact on Development and Virulence

Abstract: The thioredoxin system is of great importance for maintenance of cellular redox homeostasis. Here, we show that it has a severe influence on virulence of Botrytis cinerea, demonstrating that redox processes are important for host-pathogen interactions in this necrotrophic plant pathogen. The thioredoxin system is composed of two enzymes, the thioredoxin and the thioredoxin reductase. We identified two genes encoding for thioredoxins (bctrx1, bctrx2) and one gene encoding for a thioredoxin reductase (bctrr1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 71 publications
4
62
0
Order By: Relevance
“…As ROS are constantly formed as by-products of metabolic processes, missing or reduced detoxification due to the lack of bcskn7 could result in an accumulation of ROS. A coherence between ROS overproduction and sensitivity to external ROS could also be observed for other knockout mutants involved in the oxidative stress response, such as deletion of the thioredoxin reductase bctrr1 (55).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As ROS are constantly formed as by-products of metabolic processes, missing or reduced detoxification due to the lack of bcskn7 could result in an accumulation of ROS. A coherence between ROS overproduction and sensitivity to external ROS could also be observed for other knockout mutants involved in the oxidative stress response, such as deletion of the thioredoxin reductase bctrr1 (55).…”
Section: Discussionmentioning
confidence: 74%
“…S2C). For other mutants it could be shown that reduced growth on oxidative stress medium is accompanied by enhanced production of ROS (55). Accordingly, the mutants were tested for ROS secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SOD is required for host infection by B. cinerea, although this could be due to roles either in ROS neutralization or H 2 O 2 production (Rolke et al, 2004). Moreover, Viefhues et al (2014) showed that the thioredoxin, but not the glutathione system, is essential for survival of B. cinerea in its host. Trx1 and Trr1 were required for infection without affecting the cytosolic glutathione pool.…”
Section: Necrotrophsmentioning
confidence: 99%
“…Trx1 and Trr1 were required for infection without affecting the cytosolic glutathione pool. Conversely, the absence of glutathione reductase-responsible for recycling oxidized glutathione back to its reduces form-did not have a major effect on B. cinerea development or pathogenicity, placing it in a minor role compared to the thioredoxins and raising the question of how infection strategy affects the expression of particular antioxidation pathways (Marschall and Tudzynski, 2016d;Viefhues et al, 2014). Even within a single fungal-host system, it is difficult to form a clear understanding of the mechanisms employed by the fungus.…”
Section: Necrotrophsmentioning
confidence: 99%
“…The effect of Bcglr1 deletion was more pronounced. It could be shown that infection development on primary leaves of Phaseolous vulgaris was retarded for ∆ Bcglr1 (Viefhues et al 2014 ). This defect could be attributed to delayed conidia germination, as infections with mycelium spread in a WT manner.…”
Section: The Glutathione Systemmentioning
confidence: 99%